The association between physical activity and anxiety in college students: parallel mediation of life satisfaction and self-efficacy - Deng, Jiaxin; Liu, Yongfeng; Wang, Tong; Li, Weicheng (Frontiers in Public Health, 2024)
The association between physical activity and anxiety in college students: parallel mediation of life satisfaction and self-efficacy Abstract：Objective: To explore the functions that physical activity (PA), life satisfaction, and self-efficacy have in the process of coping with anxiety among Chinese college students, and to explore the mediating role of life satisfaction and self-efficacy in this process. Methods: Participants were 358 college students (186 males, 172 females, mean age 20.88, SD=±1.80). Psychosocial tests including the Physical Activity Rating Scale (PARS-3), College Student Life Satisfaction Scale (CSLSS), General Self-Efficacy Scale (GSES), and Generalized Anxiety Disorder Scale (GAD-7) were completed. Correlations between variables were calculated using Pearson's test. The mediation model was tested using the SPSS 26.0 PROCESS macro and regression bootstrap. Results: Physical activity showed a negative correlation with anxiety (β= -0.1617, p < 0.001), life satisfaction and self-efficacy played a role in the relationship between physical activity and anxiety. More importantly, physical activity was associated with anxiety through parallel mediating effects of life satisfaction and self-efficacy, with a total mediating effect of 55.34%. Conclusion: By increasing college students' participation in physical activity, it helps to promote the growth of their life satisfaction and self-efficacy, which is the key to reducing anxiety and promoting college students' mental health.